Monoclonal antibodies in pediatric allergy - Amelia Licari; Riccardo Castagnoli; Alessia Marseglia; Chiara Bottino; Giulia Corana; Paola Guerini; Arianna Zaroli; Silvia Caimmi; Gian Luigi Marseglia (Hygeia Press di Corridori Marinella, 2015)
Production of monoclonal antibodies (mAbs) involving human-mouse hybrid cells was first described in 1970s, but these biologics are now used for a variety of diseases including cancers, autoimmune disorders and allergic diseases. The aim of this article is to review current and future applications of mAbs, in particular focusing on anti-IgE therapy, in the field of pediatric allergy.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)